2003
DOI: 10.1007/s00737-003-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

The parent-child relationship in the context of maternal depressive mood

Abstract: The aim of this study was to examine parent-child interactions 15-18 months postpartum, in families where the mother either showed depressive symptoms two months postpartum or did not. Maternal mood was assessed with the Edinburgh Postnatal Depression Scale (EPDS). Eleven women scoring >12 (signs of depressive mood) and 14 women scoring <10 (no signs of depressive mood) on the EPDS and their partners were videotaped in parent-child interactions, assessed by the Parent Child Early Relational Assessment (PCERA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
3
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 16 publications
4
55
3
7
Order By: Relevance
“…Hagen, 2002) and quality of their fathering (e.g. Albertsson-Karlgren, Graff, & Nettelbladt, 2001), and by parenting in ways that promote stronger father-child attachments (Edhborg, Lundh, Seimyr, & Widstrom, 2003). Other studies, though, fail to identify these positive effects.…”
Section: Introductionmentioning
confidence: 95%
“…Hagen, 2002) and quality of their fathering (e.g. Albertsson-Karlgren, Graff, & Nettelbladt, 2001), and by parenting in ways that promote stronger father-child attachments (Edhborg, Lundh, Seimyr, & Widstrom, 2003). Other studies, though, fail to identify these positive effects.…”
Section: Introductionmentioning
confidence: 95%
“…2,17 Maternal depression can affect child outcome through impaired parenting, as mothers who are depressed are typically hostile and less communicative with their children than those who are not depressed. [18][19][20][21] McCarty et al found that the effect of maternal depression on disruptive (externalising) behaviour disorders in their children was mediated by a difficult mother-child relationship. 22 Covariates of parental depression, such as couple relationship discord 3 and parental alcohol misuse, 5 can also affect child development and behaviour.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…An alternative interpretation of these findings is that child problems may have caused parental psychopathology. 18,28 A child with developmental or behaviour problems can generate a stressful familial environment. It is important for health services to provide adequate support to families presenting with either parental psychopathology or child adjustment problems.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Two nurse rating scales [51,52] have been published, but are only suitable for hospital use, and do not have the precise measurements obtained by videotape analysis or ethological techniques. For 30 years, filming of mother-infant interaction during play or feeding has been used to study mother-infant interaction, and 5- to 15-min videotapes have become standard for this research [53,54,55,56,57,58,59,60,61]. So far, little attempt has been made to discriminate, in these brief behavioural samples, between impairment due to depression, obsessions of child harm or child-focused anxiety and impairment due to aversion to the infant, although Clark [62] has shown, by a state-of-the-art factor analysis in a large sample of mothers with 12-month-old children, that a measure of anger and negative affect can be obtained from a study of 5-min play.…”
Section: Assessmentmentioning
confidence: 99%